The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1038/leu.2008.123
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of plasma cell dyscrasias with lenalidomide

Abstract: Lenalidomide is an immunomodulatory drug, structurally related to thalidomide, with pleiotropic activity including antiangiogenic and antineoplastic properties. It is the product of advances in our understanding of the biology of myeloma cells, their interactions with the microenvironment and of the underlying molecular pathways. In preclinical and clinical studies, lenalidomide was more potent and less toxic than thalidomide. Subsequent phase II and III studies confirmed the activity of lenalidomide either as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 84 publications
1
28
0
1
Order By: Relevance
“…Lenalidomide needs to be used with caution in the setting of CKD, and dose reduction is mandatory, because the drug is renally cleared. Despite this information, myelosuppression and other adverse events are more common in this setting (76)(77)(78). Nonetheless, it is not directly nephrotoxic, and therefore, a low dose (e.g., 5-10 mg/d) can be used.…”
Section: Systemic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Lenalidomide needs to be used with caution in the setting of CKD, and dose reduction is mandatory, because the drug is renally cleared. Despite this information, myelosuppression and other adverse events are more common in this setting (76)(77)(78). Nonetheless, it is not directly nephrotoxic, and therefore, a low dose (e.g., 5-10 mg/d) can be used.…”
Section: Systemic Therapymentioning
confidence: 99%
“…These agents have complex mechanisms of action that include the interruption of myeloma cell growth and disruption of myeloma and bone marrow stromal cell interactions (75,76). Lenalidomide needs to be used with caution in the setting of CKD, and dose reduction is mandatory, because the drug is renally cleared.…”
Section: Systemic Therapymentioning
confidence: 99%
“…Other studies done by Rajkumar SV et al, 11 and Falco et al 16 also have reported incidence of constipation with Len-Dex regimen. The incidence of constipation in Len-Dex regimen was about 27% in the study conducted by Dimopoulos MA et al, 17 . Constipation was reported in patients on VAD regimen in study by Zhongguo Shi Yan Xue Ye Xue Za Zhi 18 .…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Efforts to improve survival in patients with amyloidosis have been facilitated by the introduction of novel agents for the treatment of amyloidosis, including thalidomide, 23 lenalidomide 24 and bortezomib. 25 Melphalan-dexamethasone has been established as a highly effective regimen in patients who are not considered candidates for auto-SCT.…”
Section: Discussionmentioning
confidence: 99%